Monitoring physiological responses to water stress in two maize varieties by infrared thermography - Zia, Shamaila; Spohrer, Klaus; Wenyong, Du; Spreer, Wolfram; Romano, Giuseppe; Xiongkui, He; M, Joachim (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: Water stress is one of the main causes of yield reductions in crops, especially in arid and semi-arid regions where the water supply is limited. ?Plant water status is frequently assessed by pre-dawn leaf water potential (